Finding the Perfect Doctor: Identifying Lesbian, Gay, Bisexual, and Transgender-Competent Physicians. - Khalili, Joshua; Leung, Lucinda B.; Diamant, Allison L. (American Journal of Public Health, 2015)
Objectives. We assessed the existence of procedures and policies for identifying lesbian, gay, bisexual, and transgender (LGBT)-competent physicians at US academic faculty practices, and sought to identify physician training programs that enhance LGBT competency. Methods. We invited all 138 Liason Committee on Medical Education-accredited US academic faculty practices to participate in a survey in 2012. We systematically assessed their procedures and policies to identify LGBT-competent physicians and their LGBT-competency training. We also assessed geographic region, funding source, and an LGBT health center in the same state. We performed univariate, bivariate, and multivariate logistic regression analyses. Results. The response rate was 50%. Few participants had existing procedures (9%) or policies (4%) to identify LGBT-competent physicians. Procedures included online directories with self-identified LGBT-competent physicians available to the public. Sixteen percent of participants reported having comprehensive LGBT-competency training, and 52% reported having no training. Of note, 80% of participants indicated interest to do more to address these issues. Conclusions. There exist both need and interest for US academic faculty practices to develop procedures, policies, and programs that improve access to LGBT-competent physicians and to train physicians to become LGBT-competent.